Understanding the impact of the external dimension on the euro area - trade, capital flows and other international macroeconomic linkages - Robert Anderton; Filippo di Mauro; Fabio Moneta (European Central Bank (ECB), 2004)
Overall, the paper underlines the difficulties in spelling out the transmission and the final effects of external shocks on the euro area, and highlights the complexity of the various direct and indirect mechanisms. We describe the main channels by which potential spillovers from external economic shocks may affect the euro area. Although the evidence is unclear on the extent to which the synchronisation of international cycles may have changed, the conclusion of the paper is that the “external dimension” of the euro area has a complex impact on economic developments in the euro area, while the relative importance of the various transmission channels may have changed rather substantially over time. Accordingly, this calls for continuous monitoring and further study of the evidence available. Finally, an efficient reaction to external shocks requires a flexible economy which allows an appropriate and rapid response to external shocks. Therefore, the continuation of structural reforms in the labour and product markets in the euro area countries is essential, and will encourage a better allocation and utilisation of capital and human resources, while enhancing the euro area's growth potential.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Kapitalmobilität; Konjunkturzusammenhang; Eurozone; EU-Staaten